2022
DOI: 10.3389/fcvm.2022.803510
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Generated β-Aminoisobutyric Acid (BAIBA) Reduces Cardiomyocyte Metabolic Stress and Apoptosis Caused by Mitochondrial Dysfunction Through the miR-208b/AMPK Pathway

Abstract: ObjectiveTo explore the cardioprotective effects of exercise-derived β-aminoisobutyric (BAIBA) on cardiomyocyte apoptosis and energy metabolism in a rat model of heart failure (HF).MethodsIn male Sprague-Dawley rats (8-week-old), myocardial infarction (MI) was used to induce HF by ligating the left anterior descending branch of the coronary artery. In the Sham group, the coronary artery was threaded but not ligated. After HF development, Sham and HF rats were exercised 60 min daily, 5 days/week on a treadmill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…BAIBA has also been reported as a potent antioxidant and antiapoptotic agent in in-vitro as well as invivo studies. [59,60] Besides this, melphalan also decreased the expression of β-tubulin in the sperm tail. Since, β-tubulin is the key cytoskeletal protein responsible for the motility of sperm; a decrease in its expression might be responsible for the perturbation of sperm motility.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…BAIBA has also been reported as a potent antioxidant and antiapoptotic agent in in-vitro as well as invivo studies. [59,60] Besides this, melphalan also decreased the expression of β-tubulin in the sperm tail. Since, β-tubulin is the key cytoskeletal protein responsible for the motility of sperm; a decrease in its expression might be responsible for the perturbation of sperm motility.…”
Section: Discussionmentioning
confidence: 89%
“…[61] An earlier study also reported that BAIBA restored the H 2 O 2 -induced MMP alterations and improved the mitochondrial biogenesis as well as functions in H9C2 cardiomyocytes mediated through miR-208b/AMPK pathway. [60] Further, the ultrastructural oxidative stress in the osteocytes, PC12 cells in-vitro as well as in diabetes-induced hepatic toxicity in vivo. [16,59,62] mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that murine contracted muscle produces the L but not the Denantiomer and that L-BAIBA has a protective effect on bone (6). A recent study of heart failure in rats showed that L-BAIBA produced during treadmill exercise has a protective effect on cardiac muscle cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…To be included in the current analyses, individuals needed to be 20-85 years of age, self-reported white and non-Hispanic, and without a self-reported major chronic disease. Individuals within each sex and each 15 year age group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)35-50, 50-65, and 65 + yrs) were ranked for their performance on the FIT Core's hand grip strength test and test of the number of chair stands completed in 30 seconds (Fig. 1A).…”
Section: Recruitment Of Human Subjectsmentioning
confidence: 99%